Women's Dominance in the Short Film Kisah di Hari Minggu - Defi Trianingsih; Dewi Fatimah Hashi; Mukhtar Najib Al-Banna; Berlian Bastian; Guru Fanani Harahap (CV. Era Digital Nusantara, 2023)
Abstract: In the domestic sphere, the stereotype about men who are stronger than women is still developing. This cannot be separated from the existence of patriarchal culture. The domination of one gender is a phenomenon that often appears in society, especially in the domestic sphere. It is also clearly represented by various media, such as movies. Currently, women in the domestic sphere realize that women are empowered figures who oppose patriarchal culture and are not easily deceived by men. This phenomenon has also been represented through various media, especially films. Film effectively conveys messages and influences the audience's views on social and cultural issues. This is because films can represent events that occur in the real world. One film that represents women as dominant figures in the domestic sphere is Adi Marsono's short film titled Kisah di Hari Minggu. Based on that phenomenon, the problem formulation proposed in this research is about how women dominate in the domestic sphere, as represented in the short film Kisah di Hari Minggu. Purpose: This research aims to determine the dominant practice of women in the domestic sphere in the short film Kisah di Hari Minggu. Design/Methodology/Approach: This is descriptive qualitative research with Sara Mills' critical discourse analysis as the approach. Findings: The research results show that both verbal and non-verbal actions in that movie show a woman's dominance, who is a mother. It also shows a counter to the patriarchal system, which always positions women under men. Originality/Value: The film analysis of women’s dominance is limited since many previous research studies focus on men’s dominance. However, this research examines how women's dominance in the domestic sphere in a short film is analyzed using critical discourse analysis methods.